Anti-Gender Politics as Discourse Coalitions: Russia's Domestic and International Promotion of "Traditional Values". Issue 2 (4th March 2023) - Edenborg, Emil
ABSTRACT: This article proposes Maarten Hajer's concept of discourse coalition for analyzing anti-gender politics and its interlinkages with other forms of opposition to sexual and gender equality. The perspective conceptualizes how actors with disparate ideological, philosophical, and religious views can communicate and produce meaningful interventions, if they share certain storylines. This primarily conceptual contribution is illustrated with a study of how "traditional values" are promoted by the Russian state. Two storylines, stressing the needs to protect "traditional values" from outside interference, and children from harmful sexual information, enable discursive affinities and interconnections across differences, domestically, internationally, and transnationally.